Evaluation of microbal colonization of the oral cavity in patients with intolerance to materials of fixed dentures. - Grizodub, D. V. (Medicni Perspektivi, 2015)
To improve prevention and treatment of intolerance to fixed denture materials by studying the impact of status of microbial contamination of the oral cavity on the pathogenesis of its development. The clinical study was performed in 62 patients, 22 of them came to the clinic for prosthetics and with clinical symptoms of intolerance to fixed dentures. The comparison group consisted of patients without clinical manifestations of intolerance. Healthy individuals without prosthesis were used as a control group. The results of clinical studies convincingly demonstrate that in the oral mucosa of patients of the main group level of Gram-negative bacteria was higher and that of Gram-positive was lower than in the comparison groups. Indicators in the study group testify to the increase in the total number of microorganisms, especially Gram-negative bacteria and decrease of gram-positive ones. Contamination with fungi of the genus Candida of the oral mucosa of patients with intolerance to materials of fixed dentures was higher by 67,3% in the main group than in the comparison group.